Effect of Kinesio® taping on static and dynamic balance after anterior cruciate ligament reconstruction: A randomized controlled trial - Sousa, João (2024)
Anterior cruciate ligament (ACL) rupture is one of the most common knee injuries among athletes (Evans and Nielson, 2022). ACL reconstruction is, in general, the solution for the rupture of ACL; the torn ligament is replaced with a tissue graft from another surrounding functional structure of the knee (Rochmania et al., 2012). The functional changes that occur after ACL reconstruction comprise deficits of muscle power, functional performance, joint proprioception, and balance (Ageberg, 2002). Evidence shows that even several months after a successful ACL reconstruction subjects still present motor control changes, influencing knee functionality (Furlanetto et al., 2016). Kinesio Taping (KT), which consists of the application of elastic adhesive bands to the skin (Oliveira et al., 2016), is frequently used in orthopedics, sports medicine, and neurological rehabilitation (Choi et al., 2016). It is used in several areas of physiotherapy to relieve pain (Nadali et al., 2014; Pamuk and Yucesoy, 2015), promote postural correction, stimulate muscle function (Cortesi et al., 2011; Lee et al., 2016; Scarborough et al., 1999), enhance gait (Choi et al., 2016; Lee et al., 2016, Yang et al., 2015), and improve balance (Bernardelli et al., 2019, Khalili et al., 2022). Despite being a technique commonly used during sports practice and in the rehabilitation of musculoskeletal and sport injuries, KT has little and insufficient evidence supporting its use to improve balance and postural control, particularly after a major musculoskeletal injury/surgery such as ACL reconstruction (Gholami et al., 2020). Moreover, only a few studies assessed the effect of KT in patients undergoing ACL reconstruction (Balki et al., 2016, Boguszewski et al., 2013; Laborie et al., 2015). Collectively, they evaluated the effects of the KT on the range of knee motion, oedema (Balki et al., 2016; Boguszewski et al., 2013), muscle strength (Balki et al., 2016), and pain (Balki et al., 2016; Boguszewski et al., 2013; Laborie et al., 2015). It is accepted that KT stimulates proprioception through cutaneous receptors by altering somatosensory information (Tamburella et al., 2014), which consequently increases the cortical excitability of the cortical motor areas of cerebral cortex (Oliveira et al., 2016). However, it is not known whether it influences balance and postural control after ACL reconstruction. We will test the application of KT for 24 h, to determine whether KT could be used to maximize balance and postural control during the rehabilitation process or when resuming sport practice to decrease the risk of re-injury. Thus, the purpose of this study was to assess the effects of KT on balance and postural control among young adults with ACL reconstruction.